KIAI TAWAKKAL AS ŽIŽEKIAN SUBJECT: READING MUSTOFA BISRI’S GUS JAKFAR IN SLAVOJ ŽIŽEK’S PERSPERCTIVE - Aliyatul Himmah (PARADIGM: Journal of Language and Literary Studies, 2019)
The paper examines the spiritual practice of Kiai Tawakkal in Gus Mus’ Gus Jakfar implementing Slavoj Žižek’s theory of subject. The articles which combine these two scientific dimensions needs to be done because there are no similar studies which have been previously conducted. In addition, by using Žižek’s theory, it is expected that readers will be able to understand Sufism from a "rational" perspective. The results of this study indicate that suluk carried out by Kiai Tawakkal explicitly breaks the symbolic boundaries adopted by Gus Jakfar and the surrounding community. This act becomes a means for Kiai Tawakkal to reach the Real, or the Haq.